Building strategic alliances in production in the seventh art: a multicase study of brazilian films producers - Gonçalves, Carlos Alberto; Silva, Everton Rodrigues; Lopes, Daniel Paulino Teixeira (Revista de Administração da UFSM, 2015)
The movie industry is characterized by the ambiguity of being an industrial activity and a symbolic to the national identity. Despite its relevance, there is a literature gap concerning the role of alliances in the national film production. We sought to understand this process through the lens of the industry structure and the resource-based view. This study was qualitative in nature on the basis of a multiple case study approach and semi-structured interviews. The findings showed that, due to the majors’ oligopolistic domain, the national industry inherited the North American pattern for revenue-sharing among participants in the production chain. However, the United States market structure is based in both vertical integration and strong ties between the movie industry and the television industry. Analyzing the Brazilian movie industry, government resignation from investing in production, reduced film lifecycles, and few projects funded privately (via incentive laws), competition between productions is fierce. We found not only that alliances are essential to the functioning of the industry (resource complementarity), but also that producers are strongly dependent to other elements in the movie value system – particularly due to power asymmetries created by the industry structure. Complementarity and dependency go hand in hand.